Triage of Acute Ischemic Stroke in Confirmed COVID-19: Large Vessel Occlusion Associated With Coronavirus Infection - Moshayedi, Pouria; Ryan, Timothy E.; Mejia, Lucido Luciano Ponce; Nour, May; Liebeskind, David S. (Frontiers in Neurology, 2020)
The outbreak of COVID-19 has posed a significant challenge to global healthcare. Acute stroke care requires rapid bedside attendance, imaging, and intervention. However, for acute stroke patients who have a diagnosis of or are under investigation for COVID-19, the concern for nosocomial transmission moderates operational procedures for acute stroke care. We present our experience with an in-hospital stroke code called on a COVID-19-positive patient with a left middle cerebral artery syndrome and the challenges faced for timely examination, imaging, and decision to intervene. The outlook for the ongoing COVID-19 pandemic necessitates the development of protocols to sustain timely and effective acute stroke care while mitigating healthcare-associated transmission.